Leadership in Interventional Radiology – Fostering a Culture of Excellence. Issue 1 (February 2023) - Brady, Adrian P.; Uberoi, Raman; Lee, Michael J.; Müller-Hülsbeck, Stefan; Adam, Andreas
This invited article reviews the current status of Interventional Radiology (IR), in terms of its status as a speciality, and outlines the conditions needed for IR to function optimally within healthcare settings. Guidance is offered in terms of developing an IR department, ensuring high-quality practice, dealing with administrative and political challenges, dealing with industry and creating a legacy.